Fashion Trend Forecasting Spirituality as an Inspiration in Creating Evening Party Dress Design Illustration Titled De Valeur - Alfitrah, Fauzan; Arifiana, Deny; Rahayu, Imami Arum Tri; Wiyono, Agus (PT. Riset Press International, 2024)
De Valeur comes from the French word which means